ChemInform Abstract: Searching for Glycomimetics that Target Protein Misfolding in Rare Diseases: Successes, Failures, and Unexpected Progress Made in Organic Synthesis. Issue 36 (9th September 2014) - Compain, Philippe
Abstract Review: [113 refs.